Is Adult Second Language Acquisition Defective? - Dąbrowska, Ewa; Becker, Laura; Miorelli, Luca (Frontiers in Psychology, 2020)
There is a large literature showing that adult L2 learners, in contrast to children, often fail to acquire native-like competence in the second language. Because of such age effects, adult L2 learning is often viewed as “fundamentally different” from child acquisition, and defective in some way. However, adult L2 learners do not always do worse than child learners. Several studies (e.g. Dąbrowska, 2019; Dąbrowska and Street, 2006; Sasaki, 1997; Street, 2017) found considerable overlap between L1 and L2 speakers’ performance on tasks tapping morphosyntactic knowledge. Crucially, these studies used grammatical comprehension tasks (e.g. picture selection) to test mastery of “functional” grammar (i.e. grammatical contrasts which correspond to a clear difference in meaning, such as the assignment of agent and patient roles in sentences with noncanonical word order and quantifier scope). In contrast, most ultimate attainment studies (e.g. DeKeyser, 2000; DeKeyser et al., 2010; Flege et al., 1999; Johnson and Newport, 1989) used a grammaticality judgment task which assessed mastery of “decorative” grammar, i.e. grammatical morphemes such as tense and agreement markers which make relatively little contribution to the meaning conveyed by a sentence. In this study, we directly compared native speakers, late immersion learners and classroom foreign language learners on tasks assessing both aspects of grammar. As in earlier studies, we found significant differences between native speakers and both non-native groups in performance on “decorative” grammar, particularly when performance was assessed using spoken rather than written stimuli. However, the differences in performance on the “functional” grammar task were much smaller and statistically non-significant. Furthermore, even in the “decorative” grammar task, there was more overlap between native speakers and late L2 learners than reported in earlier research. We argue that this is because earlier studies underestimated the amount of variation found in native speakers.